Pericardiocentesis in Clinical Practice: Indications, Technique, Patient Safety Considerations, and Nursing Roles - Falatah, Omamh Kalid; Sarah Saleem Aljohani; Noora Saad Aldrehim; Khlood Mahmoud Alkor; Arif Thaar Alotibi; Muteb Saleem Almutiri; Muteb Bin Khalid Bin Hamad Almutairi; Nora Soud Almotairi; Aisha Marie Alsayed; Ahmed Hamed Khamis Alsharari; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pericardiocentesis is a critical cardiovascular intervention for evacuating pericardial fluid, primarily indicated in cardiac tamponade and large symptomatic effusions. It serves both therapeutic and diagnostic purposes, reducing intrapericardial pressure and enabling etiologic clarification. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review the indications, anatomical considerations, procedural techniques, and safety measures associated with pericardiocentesis, emphasizing contemporary image-guided standards. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative synthesis integrates current clinical guidelines and evidence-based practices regarding pericardiocentesis. It examines anatomical relationships, physiologic principles, procedural preparation, technical approaches, and complication management strategies. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Modern practice prioritizes echocardiography-guided pericardiocentesis for enhanced accuracy and reduced risk. Indications include cardiac tamponade, large symptomatic effusions, purulent pericarditis, recurrent effusions, and traumatic hemopericardium. Contraindications are largely relative outside emergent settings, with coagulopathy and unclear diagnosis being key concerns. Complications—such as myocardial laceration, vascular injury, pneumothorax, arrhythmias, and infection—occur in approximately 5% of cases but are mitigated by imaging guidance, structured preparation, and surgical backup. Interprofessional collaboration significantly improves outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pericardiocentesis remains a life-saving procedure in acute cardiac care. Image-guided techniques, meticulous planning, and team-based execution are essential to optimize safety and efficacy.